EFFECT OF POST-HATCH FEED DEPRIVATION ON FATTY ACID COMPOSITION OF BROILER MEAT - Sugiharto, S.; Isroli, I.; Yudiarti, T.; Widiastuti, E.; Kusumanti, E. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The objective of the present study was to investigate the effect of feed deprivation over the first 48 h post-hatch on the composition of fatty acids in broiler meat. Sixty 1-d-old Ross chicks were divided to two experimental groups, i.e., birds provided access to feed and water ad libitumimmediately post-hatch until d 35 and birds deprived from feed but not from water over the first 48 h post-hatch. Blood for cholesterol analysis was collected on d 34. The same birds were sacrificed on d 36, and immediately breast meat, abdominal fat, heart and liver were collected and weighed.Feed deprivation over the first 48 h post-hatch retarded (P<0.05) growth performance of chickens, but had no impact (P>0.05) on the abdominal fat, fatty acid profile of meat, total serum cholesterol level as well as the weight of heart and liver of broiler. In conclusion, early post-hatch feeding is a beneficial means to enhance the final body weight of broilers without affecting the meat quality.